Examination of soils under grasslands in the territory of Kosjeric municipality - Anđelković Snežana; Babić Snežana; Vasić Tanja; Milenković Jasmina; Marković Jordan; Prijović Mladen; Lazarević Đorđe (Zemljište i biljka, 2019)
For successful plant production, optimum conditions for microbiological processes need to be ensured, since micro-organisms play a vital role in maintaining fertility of the soil. They respond quickly to changes in the soil ecosystem, so they represent good indicators of soil health. In order to improve plant production and proper soil use, we tested the soil quality of natural and indigenous grasslands of the Municipality of Kosjerić. Eleven samples from sown and nineteen soil samples from natural grasslands were analyzed, with chemical properties and total number of microorganisms determined. The majority of soil samples are of acidic chemical reactions, with medium humus and nitrogen content, low phosphorus content and sufficient amounts of potassium. The total number of microorganisms ranged from 5.778 to 6.431 (log of the number) per gram of absolutely dry soil.